2011
DOI: 10.1007/s00223-011-9529-6
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and Microstructure of Cortical Bone in Reconstructed Canine Mandibles After Bone Transport Distraction Osteogenesis

Abstract: Purpose Reconstruction of the canine mandible using bone transport distraction osteogenesis has been shown to be a suitable method for correcting segmental bone defects produced by cancer, gunshots, and trauma. Although the mechanical quality of the new regenerate cortical bone seems to be related to the mineralization process, several questions regarding the micro-structural patterns of the new bony tissue remain unanswered. The purpose of this study was to quantify any microstructural differences that may ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…In a study conducted at Mercer university (USA) on the architecture and microstructure of cortical bone regenerated with TDO, it was found and concluded through their study that at 12 weeks of consolidation, bone created during bone TDO was comparable to native bone in microstructure, architecture, and mechanical properties and when appropriate time has lapsed, the properties of the regenerate bone were identical to the host bone [16].…”
Section: Histologymentioning
confidence: 99%
“…In a study conducted at Mercer university (USA) on the architecture and microstructure of cortical bone regenerated with TDO, it was found and concluded through their study that at 12 weeks of consolidation, bone created during bone TDO was comparable to native bone in microstructure, architecture, and mechanical properties and when appropriate time has lapsed, the properties of the regenerate bone were identical to the host bone [16].…”
Section: Histologymentioning
confidence: 99%
“…This surgical process has been widely used not only because it has been shown that the quality of the new cortical bone created during the BTDO procedure resembles the original bone [26,31,32], but also because it allows early implants placement induced by the functional recovery of the mandible [33,34]. The present article provides evidence for a couple of biomechanical benefits of the mandibular BTDO process.…”
Section: Discussionmentioning
confidence: 88%
“…The articles which evaluated transport-disc-distraction osteogenesis used either internal or external distractors to attempt to bridge critical sized defects [17,18,21,49,50]. Authors carrying out TDDO on defects greater than 30 mm reported non-union rates between subjects at 50-100 % due to inadequate contact of the transport disc with the docking site [20,21].…”
Section: Discussionmentioning
confidence: 99%